Menstrual Justice in Immigration Detention - Gomez, Valeria; Karin, Marcy L. (Columbia Journal of Gender and Law, 2021)
The menstrual injustices experienced by noncitizens detained in immigration facilities – a particularly vulnerable subset of menstruators in carceral spaces – are largely ignored. Menstruating detainees are forced to rely on the immigration system to provide adequate access to menstrual products, and on detention facilities to engage in safe menstrual management and corresponding dignity. Unfortunately, the immigration system fails many detainees, and the defining characteristics of immigration detention— the lack of access to counsel and significant geographic and social isolation that people in custody face—exacerbate the problem. Despite these isolating factors, detainees are finding ways to share their struggles with menstrual injustices. This Essay aims to categorize, amplify, and contextualize these experiences, and the need for thoughtful reform.